Three species of Hydrobaenus Fries (Diptera: Chironomidae: Orthocladiinae) from Belarus - Makarchenko, Eugenyi A.; Makarchenko, Marina A. (Zootaxa, 2018)
Illustrated descriptions of adult male, pupa and fourth instar larva of Hydrobaenus molleri sp. nov., adult male of H. hvoenskiensis sp. nov. and redescription of adult male H. pilipes (Malloch) with taxonomic notes are provided on the basis of materials collected from Belarus.